Pendampingan Motivasi Belajar Santri dengan Pembelajaran Kitab Minhajul Muta’allimin di Pondok Pesantren Sunan Drajat Lamongan - Ulum, Miftachul; Mun'im, Abdul (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of community assistance activities is to provide assistance to SMK Sunan Drajat Lamongan class X students in motivating learning by exploring the study of the Minhajul Muta'allimin book by Imam Ghazali. The method of assistance is by reading the book of Minhajul Muta'allin with the original Arabic text translated into Javanese with pegon writing using pesantren techniques and methods of interpretation. The activity was carried out for 20 days starting from March 12-31, 2024 precisely in the month of Ramadan.  The results of mentoring activities assisted participants understand their duties and obligations as students during learning activities. Students understand how to behave and behave in the process of studying in front of teachers.  Students are motivated to be enthusiastic in learning and worshiping.